Correlation of Baba’s diabetic neuropathy classification with various diabetes-related complications - Iwamoto, Yuichiro; Nakanishi, Shuhei; Itoh, Takashi; Nakao, Erina; Sugisaki, Toshitomo; Kusano, Takashi; Ohnishi, Mana; Takenouchi, Haruka; Iwamoto, Hideyuki; Sanada, Junpei; Fushimi, Yoshiro; Katakura, Yukino; et al. (Frontiers in Endocrinology, 2022)
It is known that Baba's diabetic neuropathy classification (BDC) is useful in quantitative evaluation of Diabetic polyneuropathy (DPN). In this study, we aimed to investigate the possible association between BDC and various diabetic microvascular and macrovascular complications in patients whose neuropathy was evaluated with BDC. As the results, BDC was significantly correlated with the progression of diabetic retinopathy and nephropathy. BDC was also significantly correlated with history of myocardial infarction or cerebral infarction, carotid IMT, and ABI. These data suggest that BDC may be useful in predicting the presence of various diabetic microvascular and macrovascular complications. The data also support the idea that we should perform further investigation of other diabetes-related complications in patients with severe DPN.